If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r + -6 = 1r + 3 Reorder the terms: -6 + 5r = 1r + 3 Reorder the terms: -6 + 5r = 3 + 1r Solving -6 + 5r = 3 + 1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -6 + 5r + -1r = 3 + 1r + -1r Combine like terms: 5r + -1r = 4r -6 + 4r = 3 + 1r + -1r Combine like terms: 1r + -1r = 0 -6 + 4r = 3 + 0 -6 + 4r = 3 Add '6' to each side of the equation. -6 + 6 + 4r = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 4r = 3 + 6 4r = 3 + 6 Combine like terms: 3 + 6 = 9 4r = 9 Divide each side by '4'. r = 2.25 Simplifying r = 2.25
| z=4x-4 | | 0=7h^2+10h+3 | | 7/5x | | 5x+47=-1-3x | | 2x+3x+5=50 | | a+54=180-2a | | 4k-9=7k | | 7-2x=2-4 | | (x^-2/4x^-6)^-2 | | 3x-9/40 | | 1-4k-2=-8k | | 7+-8c-48= | | 7(2x-10)-(5-7x)= | | h1/3-4=13 | | 16m^4-25m^2+9= | | 30/4.10 | | 5x+21=6x | | 4x+20=22x-12 | | 50x-5+6x+128+35x+60x=540 | | 56(56-20/4) | | t=(3x+4)(2x-5) | | 2x-3-5= | | x^8+x^4-2= | | 2-5(a-1)=9+a | | 2x-6=5-3 | | a^2x^2+b^2y^2-b^2x^2-a^2y^2= | | (4-w)(3w+2)=0 | | 10.5+6x+7.5=21 | | lx+6l=19 | | 0=3x^2-16x+5 | | 24=3(n-4) | | 56(56-2x/4) |